Diagnostic performance of the Strength and Pain Assessment (SPA) score for non-contact muscle injury screening in male soccer players - Semperboni, L.; Vignati, C.; Ballatore, M. G.; Tabacco, A.; Busso, C.; Minetto, M. A. (The Physician and Sportsmedicine, 2021)
Objectives The aims of this study were to develop a clinical-feature based scoring system for muscle injury screening and to assess its diagnostic accuracy when large number of injuries are suspected.